Diet and sex modify exercise and cardiac adaptation in the mouse - Konhilas, John P. (Am J Physiol Heart Circ Physiol, 2014)
The heart adapts to exercise stimuli in a sex-dimorphic manner when mice are fed the traditional soy-based chow. Females undergo more voluntary exercise (4 wk) than males and exhibit more cardiac hypertrophy per kilometer run (18, 32). We have found that diet plays a critical role in cage wheel exercise and cardiac adaptation to the exercise stimulus in this sex dimorphism. Specifically, feeding male mice a casein-based, soy-free diet increases daily running distance over soy-fed counterparts to equal that of females. Moreover, casein-fed males have a greater capacity to increase their cardiac mass in response to exercise compared with soy-fed males. To further explore the biochemical mechanisms for these differences, we performed a candidate-based RT-PCR screen on genes previously implicated in diet- or exercise-based cardiac hypertrophy. Of the genes screened, many exhibit significant exercise, diet, or sex effects but only transforming growth factor-β1 shows a significant three-way interaction with no genes showing a two-way interaction. Finally, we show that the expression and activity of adenosine monophosphate-activated kinase-α2 and acetyl-CoA carboxylase is dependent on exercise, diet, and sex.